Notes on the state of ophthalmology in the ancient Egypt - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The article presents the state of ophthalmological knowledge in the ancient Egypt. Medical and ophthalmological information included in Smith's and Ebers papyruses are discussed. The first ever known ophthalmologist by the name of Iry is mentioned. The article also presents the history of medical school in Alexandria.